Digital Health and Wearable Technologies (Kindle, 2024)
Digital health and wearable technologies represent a transformative wave in healthcare, blending medical advancements with innovative technology to enhance patient care, monitor health conditions, and promote wellness. These technologies encompass a wide range of devices, from fitness trackers and smartwatches to sophisticated medical devices designed for continuous health monitoring. Wearable technologies, such as smartwatches and fitness bands, are equipped with sensors that track various health metrics, including heart rate, steps taken, calories burned, sleep patterns, and even blood oxygen levels. These devices provide real-time data, empowering individuals to make informed decisions about their health and lifestyle. The integration of wearable technology with smartphone applications allows for the seamless transfer and analysis of health data, fostering a proactive approach to personal health management. In the realm of clinical healthcare, wearable technologies are revolutionizing patient monitoring and management. Devices such as continuous glucose monitors and wearable ECGs offer patients and healthcare providers critical insights into chronic conditions, enabling timely interventions and personalized treatment plans. Remote patient monitoring, facilitated by these wearables, reduces the need for frequent hospital visits, thus improving patient convenience and reducing healthcare costs. Moreover, the data collected from wearable devices contribute to a vast repository of health information, advancing research and development in preventive medicine and chronic disease management. As digital health and wearable technologies continue to evolve, they hold the promise of more efficient, personalized, and accessible healthcare, ultimately enhancing the quality of life for individuals worldwide.
Keywords: Digital Health; Wearable Technologies